IPO and Economic Performance of SMEs: The Case of SMEs Listed on the Casablanca Stock Exchange - EL AAROUBI , Siraj; EL AZZOUZI , Rami (Revue du contrôle, de la comptabilité et de l’audit, 2022)
Today, the Moroccan capital market presents significant financing opportunities for SMEs, whether to finance their investment or operating cycle. In addition to the advantages offered by the financial market, the listing on the stock exchange may involve constraints inducing explicit costs and others of an implicit nature that may influence the medium and long-term performance of the company introduced. This article aims to assess the impact of the IPO on the economic performance of SMEs. To this end, we examined the theoretical foundation of the agency, the signal, and the behavioral model of timing. By studying a sample of eight SMEs introduced on the stock exchange between 2004 and 2016, via an event study, it emerges that the companies in the sample outperformed the year before an IPO and underperformed after listing, except that this underperformance is not statistically significant.